Enhancing UMKM Sales and Exports Through Product Labeling Support - Rosyid, Ahmad Sihabudin; Mustofa, Ahmad Ihzal; Alfani, Ajeng Khori; Putra, Bayu; Nur Aisyah, Irna Nissa; Nirmala, Maiyuni; Amara, Ressa; Saputra, Rizki Maulana; Munir, Sahrul; Maghfiroh, Ummu; Majid, Wahid Abdul; Zuniati, Mai (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
This community service initiative assists SMEs in Desa Raman Fajar with product labeling to enhance sales turnover and export potential. The underlying issue is business owners' lack of awareness and understanding regarding the importance of product labeling as a branding strategy. Labels serve as the product's identity, providing essential information about the origin and manufacturer, thereby increasing consumer trust and market reach. The service employs the Asset-Based Community Development (ABCD) method, leveraging local resources such as cassava to empower local businesses. The partnership involves a related business owner in Dusun 8, Desa Raman Fajar. The community service results indicate a significant increase in the partner's knowledge of labeling and branding strategies. The partner actively participated in the labeling process from start to finish, demonstrating enthusiasm and commitment. Data collection involved direct observation and interviews with a single business subject, while data analysis utilized qualitative approaches to assess improvements in branding knowledge and business outcomes. As a result, the business owner reported a 20% increase in sales turnover within three months of implementing the new labeling strategy, showcasing the initiative's effectiveness. This research highlights the critical role of product labeling in enhancing SME visibility and competitiveness in local and export markets.